De-Coalizing Rural China: A Critical Examination of the Coal to Clean Heating Project from a Policy Process Perspective - Hu, Zhanping (Frontiers in Energy Research, 2021)
This article critically examines the Coal to Clean Heating Project (CCHP) implemented in rural northern China from a policy process perspective. On the one hand, CCHP is an effective environmental policy that has reduced a large quantity of low quality bulk coal; on the other hand, however, it has created mounting socio-economic and political challenges, pushing the well-intended project into a deep dilemma. Moreover, existent discussions tend to attribute the dilemma to the “inappropriate implementation” of street-level bureaucrats. Through the lens of policy process, this article identifies key features of five critical temporal stages of CCHP: agenda setting, policy formulation, policy implementation, policy evaluation and policy adjustment. It illustrates that the policy process of CCHP has followed a politics-administration-dominated approach characterized by both positive attributes such as rapid resource mobilization and efficient implementation, and negative factors such as deficient policy design, overuse of mandatory instruments, and neglect of social acceptance. The major challenges that CCHP currently faces are identified, and policy implications are proposed based on the insights drawn from the policy process perspective. It concludes by highlighting the complexity of energy transition and the strength of linking energy transition research with a policy process perspective.